Contribution of Goat Manure Organic Fertilizer to the Number of Rice (Oryza sativa L.) Tillers - Sunarsan, Debra Fortuna; Anhar, Azwir; Kardiman, Reki; Vauzia, Vauzia (Department of Biology, Faculty of Mathematics and Natural Sciences, Universitas Negeri Padang, 2024)
The relatively high and continuous use of inorganic fertilizers in rice cultivation can cause negative impacts on the environment. Minister of Agriculture Regulation Number: 40/2007 recommends providing organic fertilizer combined with inorganic fertilizer with the aim of improving soil condition and fertility. This research aims to determine the effect of the composition of organic goat manure and inorganic fertilizer on the number of rice tillers. This research was structured using a Completely Randomized Design. The treatment given was a comparison of organic fertilizer to inorganic fertilizer consisting of 6 treatments and 4 replications. The treatments given consisted of A(100% NPK Fertilizer + 0% Goat Manure Fertilizer), B(80% NPK Fertilizer + 20% Goat Manure Fertilizer), C(60% NPK Fertilizer + 40% Goat Manure Fertilizer), D(40% NPK Fertilizer + 60% Goat Manure Fertilizer), E(20% NPK Fertilizer + 80% Goat Manure Fertilizer), F(0% NPK Fertilizer + 100% Goat Manure Fertilizer). Observational data was analyzed by analysis of variance (ANOVA) using the SPSS application. The results showed that the use of inorganic NPK fertilizer combined with organic goat manure had no significant effect on the number of offspring. The composition of inorganic NPK fertilizer and organic goat manure gave the same response to the number of rice tillers.